Psalm 91 in early North American Pentecostal periodicals: A reception history from 1906 to 1939 - Lee Roy Martin (Pharos Journal of Theology)
This reception history aims to locate Psalm 91 within the Pentecostal context and to discover the effects of the psalm on Pentecostal theology and practice. The study examines North American periodicals from the beginning of 1906 (the start of the Azusa St. revival) to the end of 1939, a period that historian Walter J. Hollenweger describes as the “heart” of the Pentecostal movement. These early voices help to shape a Pentecostal approach to the Psalms, as they show how this segment of the first generation of Pentecostals struggled with issues of faith, trust, disease, healing, persecution, and prayer. The testimonies, sermons, and articles reviewed here demonstrate that early Pentecostals read the Psalms confessionally and through the lens of Pentecostal theology, spirituality, and experience. Therefore, Pentecostals employed a variety of hermeneutical approaches. They read the Psalms historically, theologically, typologically, and spiritually. To early Pentecostals, Psalm 91 was a declaration of God’s promises to care for his people, to protect them from harm, and to be with them in times of trouble. The psalm generated faith, hope, confidence, and gratitude in the hearer. However, the more discerning hearers knew that Psalm 91 is a confession of faith, not a theological treatise. Thus, they interpreted the promises of God as genuine but not as absolutes.